2007
DOI: 10.1186/1471-2202-8-52
|View full text |Cite
|
Sign up to set email alerts
|

Semantic, syntactic, and phonological processing of written words in adult developmental dyslexic readers: an event-related brain potential study

Abstract: Background: The present study used event-related brain potentials to investigate semantic, phonological and syntactic processes in adult German dyslexic and normal readers in a word reading task. Pairs of German words were presented one word at a time. Subjects had to perform a semantic judgment task (house -window; are they semantically related?), a rhyme judgment task (house -mouse; do they rhyme?) and a gender judgment task (das -Haus [the -house]; is the gender correct? [in German, house has a neutral gend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
49
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 74 publications
(64 reference statements)
8
49
0
4
Order By: Relevance
“…This result is consistent with those obtained on other explicit phonological awareness measures, most of which are in the N400 range (e.g., auditory and visual rhyming; Ackerman, Dykman, & Oglesby, 1994;McPherson & Ackerman, 1999;McPherson, Ackerman, Holcomb, & Dykman, 1998;Rüsseler, Becker, Johannes, & Münte, 2007; see also Jednoróga, Marchewkaa, Tacikowskia, & Grabowska, 2010). It is also compatible with the hypothesis that dyslexics fail to adequately develop phonological skills, as well as an under-activation of temporo-parietal areas (Georgiewa et al, 2002;Shaywitz et al, 2001; see Richlan, Kronbichler, & Wimmer, 2009, for a review) or less engagement of the left hemisphere in these readers (e.g., Araújo et al, 2012;Pugh et al, 2000;Shaywitz et al, 2001).…”
Section: Discussionsupporting
confidence: 81%
“…This result is consistent with those obtained on other explicit phonological awareness measures, most of which are in the N400 range (e.g., auditory and visual rhyming; Ackerman, Dykman, & Oglesby, 1994;McPherson & Ackerman, 1999;McPherson, Ackerman, Holcomb, & Dykman, 1998;Rüsseler, Becker, Johannes, & Münte, 2007; see also Jednoróga, Marchewkaa, Tacikowskia, & Grabowska, 2010). It is also compatible with the hypothesis that dyslexics fail to adequately develop phonological skills, as well as an under-activation of temporo-parietal areas (Georgiewa et al, 2002;Shaywitz et al, 2001; see Richlan, Kronbichler, & Wimmer, 2009, for a review) or less engagement of the left hemisphere in these readers (e.g., Araújo et al, 2012;Pugh et al, 2000;Shaywitz et al, 2001).…”
Section: Discussionsupporting
confidence: 81%
“…An additional four studies have examined responses to words preceded by single items that were semantically related or unrelated. Similar to the sentence congruity results, three of these studies obtained smaller N400 effects in children with developmental learning disabilities (Stelmack and Miles, 1990;Miles and Stelmack, 1994;Plante et al, 2000); whereas one reported no difference between dyslexic and control subjects (Rüsseler et al, 2007). Overall, small or delayed N400 effects in learning-disabled subjects comprise some three-quarters of published reports using a semantic context manipulation.…”
Section: Developmental Learning Disabilitiessupporting
confidence: 58%
“…Ackerman et al (1994) also observed, in subjects with dyslexia, a small rhyme effect when judging printed word pairs, but paradoxically, a normal rhyme effect when judging pseudo word pairs. Only Rüsseler et al (2007) used both semantic and rhyme manipulations in the same participants: They observed no amplitude differences between dyslexic and control groups, but a slight latency delay in the former group for the rhyme effect only. Clarification of the relationship between rhyme and semantic N400 effects in individuals with learning disabilities requires further research.…”
Section: Developmental Learning Disabilitiesmentioning
confidence: 99%
“…It thus seems unlikely that their naming impairments stem from a selective deficit in semantic access/retrieval and integration of semantic information, as suggested already by some behavioral studies (Faust and SharfsteinFriedman, 2003;Murphy and Pollatsek, 1988). Electrophysiological studies on semantic processing in subjects with reading disorders are scarce (to our knowledge, none with naming tasks) and have yielded rather mixed results (Jednoróg et al, 2010;Rüsseler et al, 2007;Schulz et al, 2008;Silva-Pereyra et al, 2003). Some studies on sentence processing have reported an attenuation of N400 effect in semantic priming in dyslexics compared to controls (Helenius et al, 1999;Schulz et al, 2008; but see also Robichon et al (2002) for enhanced N400) whereas others have found semantic priming to be relatively intact in individuals with dyslexia (Jednoróg et al, 2010).…”
Section: Semantic Relationshipmentioning
confidence: 81%